Promotion Mix Effect On The Decision Purchase Hijab MonocromeIn Surakarta - Pradana, Vieka Dyah Ayu, Ma'ruf, SE., MM (2017)
This research aim to 1) To know the influence among variable advertising to decision purchasing of product Hijab Monocrome in Surakarta 2) To know the influence among variable of personal selling to decision purchasing of product Hijab Monocrome in Surakarta 3) To know the influence among variable of sales promotion to decision purchasing of product Hijab Monocrome in Surakarta. This research population all consumer Hijab Monocrome in Surakarta. Sample in this research consumer Hijab Monocrome in Surakarta that is as much 100 responder. Result of known linear regression as follows: Y = 0,101 + 0,413X1 + 0,262X2 + 0,287X3. As for linear regression equation of the following at: coefficient regresi variable Advertising (X1) equal to 0,413 which its meaning is variable Advertising have the influence positip so that improve the purchasing decision. Coefficient regresi of variable Personal Selling (X2) equal to 0,262 meaning variable of Personal Selling have the influence positip so that improve the purchasing decision. Coefficient regresi variable Sales Promotion (X3) equal to 0,287 which its meaning variable of Sales Promotion have the influence positip so that improve the purchasing decision. Result of analysis test the t obtained variable advertising have the influence which signifikance to purchasing decision. Variable of personal selling have the influence which signifikan to purchasing decision. Sales Promotion have the influence which signifikan to decision of purchasing hijab monocrome in Surakarta. Result of test F obtained by together variable Advertising (X1), Personal Selling (X2), Sales Promotion (X3) have an effect on the signifikan to purchasing decision. Result of R square ( R2) equal to 0,541, meaning variation of change of explainable purchasing decision variable by variable Advertising (X1), Personal Selling (X2), Sales Promotion (X3) equal to 54,1%. While the rest equal to 45,9% explained by other variable outside model